Nekyia - Bagadiong, Ma. Jacquelyn S.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
Nekyia means "descent into hell." It is a term used by Carl Jung when he refers to Picasso's work. He regards it as an important process in the development of a person. For only by undertaking this journey could an individual ever hope to come to term with himself/herself. The journey is what our lead character had to go through in this film. The film revolves around our lead character looking at herself in front of the mirror as she recalls her experiences. Each part of her face is a symbol of what she went through. Her different experiences and the choices she made, make up all the puzzles in her face. She may have acquired her eyes from her mother but the rest is a result of her way of adjusting to her environment and the way she chose to be. She explores and discovers reality and as she becomes part of it by learning things and acquiring those parts from those experiences. Her hideous face is a symbol of what we all are underneath our pretenses. This is the fact that no matter how revolting our experiences may seem to be, these are the things that make us whole and beautiful. The ugliness that we have underneath is what makes us truly human and unique in our own way. The film is shot using a Hi-8 video camera with overlays of 3d animation since I feel that the best way to show the development of the face of the character would be through this medium.
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman
Keywords: Nekyia (Short films -- Philippines).; False personation